Comparative accuracy of NT-proBNP and MR-proANP for the diagnosis of acute heart failure in dyspnoeic patients - Darche, Fabrice Fernand; Baumgärtner, Christian; Biener, Moritz; Müller-Hennessen, Matthias; Vafaie, Mehrshad; Koch, Vitali; Stoyanov, Kiril M.; Rivinius, Rasmus; Katus, Hugo; Giannitsis, Evangelos (ESC heart failure, 2017)
Aims To compare the performance of the natriuretic peptides (NPs) NT-proBNP and MR-proANP for the diagnosis of acute heart failure (AHF) in subsets of conditions potentially confounding the interpretation of NPs. Methods and results We studied 312 patients, presenting to the emergency department with new onset of dyspnoea or worsening of chronic dyspnoea within the last 2 weeks. Performance of NPs for the diagnosis of AHF was tested and compared using C-statistics in the entire cohort and in conditions previously described to confound interpretation of NPs such as older age, renal failure, obesity, atrial fibrillation or paced rhythm, and in the NT-proBNP grey zone. AHF was diagnosed in 139 patients. In the entire cohort, the diagnostic performance of NT-proBNP was comparable with that of MR-proANP. Receiver operating characteristic analysis demonstrated that optimal diagnostic cut-offs were higher in the presence of older age, kidney failure or rhythm disorder. However, there were no statistically relevant differences between the receiver operating characteristic curves analysed in the total population and those studied in the pre-specified subsets severe kidney failure, advanced age, obesity, atrial fibrillation and paced rhythm, and grey zone NT-proBNP values. Moreover, the diagnostic performance of NT-proBNP was comparable with that of MR-proANP in the subsets. Conclusions The performance of NT-proBNP and MR-proANP for AHF is comparable in the total population as well as in the subsets with potentially confounding characteristics such as older age, renal dysfunction, obesity, atrial fibrillation and paced rhythm, or those with NT-proBNP values in the grey zone.